New psychoactive substance use among regular psychostimulant users in Australia, 2010–2015. (1st April 2016) - Sutherland, Rachel; Peacock, Amy; Whittaker, Elizabeth; Roxburgh, Amanda; Lenton, Simon; Matthews, Allison; Butler, Kerryn; Nelson, Marina; Burns, Lucinda; Bruno, Raimondo
Highlights: Recent use of 'any' new psychoactive substance (NPS) increased from 33% in 2010 to 40% in 2015. However, rates of use varied considerably across NPS classes. Participants appeared to seek out NPS that were similar to the illicit drugs they were already using. 'Poly' NPS users were found to be a particularly high risk group of users. Abstract: Objective: To examine the rates and patterns of new psychoactive substance (NPS) use amongst regular psychostimulant users (RPU) in Australia. Method: Data were obtained from the 2010–2015 Ecstasy and related Drugs Reporting System (EDRS), which comprised a total cross-sectional sample of 4122 RPU. Results: Recent use of 'any' NPS increased from 33% in 2010 to 40% in 2015, although trends of use differed significantly across NPS classes. The correlates associated with NPS use also varied across NPS classes: frequent (i.e. weekly or more) ecstasy users were more likely to report recent phenethylamine use; LSD users were more likely to report recent phenethylamine and tryptamine use; and daily cannabis users were more likely to report recent synthetic cannabinoid use than RPU who had not used NPS. 'Poly' NPS consumers were found to be a particularly high risk group and were significantly more likely to be younger, male, report daily cannabis use, report weekly or more ecstasy use, report recent LSD use, have higher levels of poly drug use, have overdosed on any drug in the past year, and to have engaged in past month criminal activity. Conclusion: NPS use has been established as a significant and ongoing practice amongst our sample of RPU. It appears that RPU seek out NPS with similar properties to the illicit drugs that they are already consuming, with poly NPS consumers found to be a particularly high risk group.